Unicameral Bone Cyst in the Proximal Humerus with Secondary Infection in an 18-Month-Old Foal - Maria C. Fugazzola; Christoph Klaus; Christoph Lischer (Case Reports in Veterinary Medicine)
An 18-month-old warmblood filly was 4/5 lame on the front right limb at referral and showed severe swelling of the right shoulder region and pain during manipulation of the shoulder region. Radiography revealed a roundish 5 × 7 cm radiolucent area with defined borders within the greater tubercle and the presence of a fracture of the lateral tubercle associated with the cyst. Cellular blood count was 27,500 WBC/μL and serum biochemical analyses revealed fibrinogen of 855 mg/dL. The fractured bone was removed surgically; the cyst debrided and filled with autologous cancellous bone graft. Three and five weeks after surgery the filly was reoperated on because of an osseous sequestrum and a periostal defect on the distal dorsolateral aspect of the pastern of the right hind limb and a septic synovitis of the DFTS of the left hind limb. Fifteen month after surgery the filly was not lame and was introduced to training. Unicameral bone cysts (UBC) are well described lesions, often associated to pathologic fracture in the proximal humerus of children but, until present, no scientific report exists of UBC in the foal. The prompt surgical management had a favorable outcome.